Diagnosis of Pneumoconiosis with Machine Learning - (:unkn) unknown (IEEE, 2024)
Pneumoconiosis encompasses a group of lung diseases caused by inhaling dust particles. Frequently recognized as an occupational disease, it primarily affects workers in the mining industry. This paper details the use of machine learning algorithms to aut...
Keywords: Neumoconiosis; Aprendizaje automático